ULTRASONOGRAPHIC STUDY OF OVARIAN FOLLICULAR DYNAMICS IN JERSEY CROSSBRED COWS - S. Satheshkumar (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Ovarian follicular developmental pattern in Jersey crossbred (Bos indicus x Bos Taurus) cows was studied. Ultrasonographic monitoring of ovarian follicular development throughout the oestrous cycle revealed that out of six cows, three (50%) cows exhibited two waves (days of emergence on 1.33 + 0.90 & 10.0 + 0.34) and three (50%) exhibited three waves per cycle ( days of emergence on 1.67 + 0.34, 9.67 + 0.67 & 15.33 + 0.88) and the mean length of oestrous cycle was 22.50+ 0.83 days. The mean maximum diameter of final wave dominant (ovulatory) follicle was larger than the anovulatory dominant follicles of previous waves. A comparatively slower growth rate of ovulatory wave dominant follicle was recorded in our study. It was found that, 57.14 per cent of dominant follicles developed in the ovary having corpus luteum than the contralteral ovary.